Distribución y abundancia de organismos coralívoros en los arrecifes coralinos de la Isla del Caño, Costa Rica - Guzmán, Héctor M. (Revista de Biología Tropical, 1988)
During 1985 and 1986, censuses of the most abundant corallivore organisms were made at Caño Island reef, Costa Rica. These are the fishes Arothron meleagris, A. hispidus, Pseuaobalistes naufragzum, Sufflamen verres, Stegastes acapulcoensis and Microspathodon dorsalis; the gastropods Jenneria pustulata and Quoyula monodonta; the hermit crabs Trizopagurus magnificus and Aniculus elegans; and the equinoderms Acanthaster planci, Eucidaris thouarsii and Diadema mexicanum. The population densities of all species increased toward the year 1986, and their distribution across the different reef zones, i.e. reef flat, slope and base, was very similar between both years. The high densities of balistid fishes and damselfishes and their behavior may affect the abundance and distribution of other corallivore species. Since the high mortality of pocilloporid corals caused by the 1982/83 "El Niño" and the red tide (1985) events, corallivores such as hermit crabs, puffer fishes and the gastropod Quoyula, which feed mainly upon the coral Pocillopora, may have had a limiting effect on the recovery, growth and distribution of this species on the reef. On the other hand, the abundance of balistids on the reefs seems to favor the dispersion of the dominant coral species Porites lobata via fragmentation.